2021
DOI: 10.1177/01626434211019393
|View full text |Cite
|
Sign up to set email alerts
|

Personal, Cultural, and Institutional Perspectives of Special Education Technology Integrators: A Narrative Inquiry

Abstract: The purpose of this narrative inquiry was to gain a deep understanding of the lived experiences of four special education technology integrators from personal, cultural, and institutional perspectives. Two semi-structured, recorded interviews were conducted with each participant, followed by a focus group with all participants. Data analysis included continuous memoing, coding, cross coding, raw data triangulation, investigator triangulation, and member checking as a means of deeply understanding participant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Data analyses may explore themes of the content of the story, how the story was told, or to whom the story was directed (Riessman, 2008). For an example of a narrative inquiry in special education, see Courduff and Moktari's (2021) study of the stories of special educators identified as being effective at integrating technology into their practice.…”
Section: Narrative Inquirymentioning
confidence: 99%
“…Data analyses may explore themes of the content of the story, how the story was told, or to whom the story was directed (Riessman, 2008). For an example of a narrative inquiry in special education, see Courduff and Moktari's (2021) study of the stories of special educators identified as being effective at integrating technology into their practice.…”
Section: Narrative Inquirymentioning
confidence: 99%
“…Research methodologies that offer deeper and more expansive views of how entangled human and non-human bodies intra-act in school settings have the potential to support initial preparation and professional learning for teachers in digital spaces that do not assume the teacher is the only agent in the space (Courduff & Moktari, 2021; Harris & Leonardo, 2018; Redding, 2019; Rice, 2021). One such methodology is narrative inquiry, where researchers and teachers live alongside one another and collaboratively examine constellations of identity-making stories that are interwoven in school spaces (Clandinin, 1985; Clandinin, 2016; Clandinin & Connolly, 1986; Craig & Huber, 2007).…”
mentioning
confidence: 99%
“…Previous research has highlighted the importance of students’ social identities in special education (e.g., Gay, 2002; Klingner et al, 2005). A few studies have described teachers’ intersectional identities and their understandings of those identities in relation to those of their students (Bettini, Walraven, Billingsley, & Williams, 2018; Boveda & Aronson, 2019; Courduff & Moktari, 2021; Goodley, Lawthom, Liddiard, & Runswick-Cole, 2019; Wood & Happé, 2021). However, those studies have not engaged with the intra-active entangled nature of the identities of students and teachers in these spaces.…”
mentioning
confidence: 99%